2016
DOI: 10.1038/pr.2016.149
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of cannabidiol after global hypoxia-ischemia in newborn piglets

Abstract: In contrast to previous studies, we do not find significant protective effects of CBD after HI in piglets. Evaluation of CBD in higher doses might be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 39 publications
(61 reference statements)
1
38
1
Order By: Relevance
“…We recently studied the effects of CBD 1 mg/kg i.v. in a piglet model of global HI [10], and in contrast to previous studies in piglets [2,3,4,5] no neuroprotective effects were found in the early phase after HI. The hypoxic-ischemic insult in our model produces more severe multiorgan damage compared to these studies [2,3,4,5].…”
Section: Introductioncontrasting
confidence: 85%
See 4 more Smart Citations
“…We recently studied the effects of CBD 1 mg/kg i.v. in a piglet model of global HI [10], and in contrast to previous studies in piglets [2,3,4,5] no neuroprotective effects were found in the early phase after HI. The hypoxic-ischemic insult in our model produces more severe multiorgan damage compared to these studies [2,3,4,5].…”
Section: Introductioncontrasting
confidence: 85%
“…However, these models did not induce severe global HI. Cardiovascular dysfunction in the current animal model is demonstrated by severe hypotension during HI, and in the recovery phase a degree of persistent hypotension and tachycardia, as well as significantly elevated plasma troponin T [10]. High-dose CBD did not induce cardiac arrhythmias or significant alterations in heart rate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations